1975
DOI: 10.1007/bf00429545
|View full text |Cite
|
Sign up to set email alerts
|

The effects of nicotine on two-way avoidance conditioning in bi-directionally selected strains of rats

Abstract: Rats of both sexes from the genetically selected Roman High Avoidance (RHA), the Roman Low Avoidance (RLA) and the Roman Control (RCA) strains were given one 30-min session of two-way escape-avoidance conditioning (30 trials) in a shuttle box with a buzzer as the conditioned stimulus and shock as the unconditioned stimulus in a factorial design involving three time intervals (0, 15 and 30 min) following one subcutaneous injection of saline or of nicotine in five doses (0.05, 0.1, 0.2, 0.4, or 0.8 mg/kg of body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1977
1977
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Consistent with the emotion-reduction hypothesis, Hutchinson and Emley (1973) found what might be considered one of the best correlates of anxiety-conditioned suppression of positively reinforced behavior-to be reduced by low and intermediate doses of nicotine (.1-.4 mg/kg) administered subcutaneously in monkeys and rats. Also consistent with the suggestion that nicotine reduces anxiety are the findings of studies that have shown increased mobility and exploratory behavior in threatening environments, that is, in shock avoidance conditions (Fleming & Broadhurst, 1975;Morrison & Stephenson, 1972). These studies showing a reduction of the suppression of operant behavior, however, cannot be cited as strong support indicative of nicotine-induced reduction of anxiety-fear, since nicotine also increases a wide variety of operant behaviors not related to negative emotions.…”
Section: Tranquilizing and Emotion-reducing Effects Of Nicotinesupporting
confidence: 66%
See 1 more Smart Citation
“…Consistent with the emotion-reduction hypothesis, Hutchinson and Emley (1973) found what might be considered one of the best correlates of anxiety-conditioned suppression of positively reinforced behavior-to be reduced by low and intermediate doses of nicotine (.1-.4 mg/kg) administered subcutaneously in monkeys and rats. Also consistent with the suggestion that nicotine reduces anxiety are the findings of studies that have shown increased mobility and exploratory behavior in threatening environments, that is, in shock avoidance conditions (Fleming & Broadhurst, 1975;Morrison & Stephenson, 1972). These studies showing a reduction of the suppression of operant behavior, however, cannot be cited as strong support indicative of nicotine-induced reduction of anxiety-fear, since nicotine also increases a wide variety of operant behaviors not related to negative emotions.…”
Section: Tranquilizing and Emotion-reducing Effects Of Nicotinesupporting
confidence: 66%
“…Indices of fear and anxiety in animals have typically been reduced by nicotine, but these effects have been less consistent than the effects of nicotine on aggression. A number of researchers (Bovet, Bovet-Nitti, & Oliverio, 1966;Essman & Essman, 1971;Fleming & Broadhurst, 1975;Hutchinson & Emley, 1973;Morrison & Stephenson, 1972) have reported that nicotine reduces measures of anxiety (immobility, conditioned suppression, exploratory behavior) in a variety of animals. On the other hand, Davis, Kensler, and Dews (1973) and Driscoll and his coworkers (Driscoll, 1976;Driscoll & Battig, 1970;Driscoll & Battig, 1974) have reported nicotine-produced increases in indices of anxiety-fear (punishment-induced suppression of operant behavior and avoidance behavior).…”
Section: Tranquilizing and Emotion-reducing Effects Of Nicotinementioning
confidence: 99%
“…If one can identify other behavioral characteristics that are associated with a phenotype, one can then conduct behaviorgenetic analyses to determine whether those associated behaviors reflect a common biological mechanism underlying the phenotype (Broadhurst, 1975;Hirsch, 1967;Wahlsten, 1972Wahlsten, , 1978. For example, animals of the Roman high-avoidance (RHA) line (Bignami, 1965), which were selectively bred for good shuttle box avoidance behavior, are more active in the open field and make more ITRs in the shuttle box than do the Roman low-avoidance (RLA) animals, which were selectively bred for poor avoidance performance (Broadhurst & Bignami, 1965;Fleming & Broadhurst, 1975;Holland & Gupta, 1966;Satinder, 1971Satinder, , 1972. Thus, it is possible that Bignami's breeding program, although based on differences in avoidance behavior, could have selected for differences in locomotdr activity, which could account for the difference in avoidance performance.…”
mentioning
confidence: 99%
“…The Roman High and Low Avoidance strains of rats [79] display differential responses to nicotine in various assays [80] including locomotor activation [81], although other responses to nicotine, such as avoidance behavior, were not different between the two lines [82]. Variability in function of the adrenergic system seems to underlie many of the differences between these two lines [83].…”
Section: Inbred/selected Strainsmentioning
confidence: 99%